Five-Year Follow-Up After Catheter Ablation of Persistent Atrial Fibrillation Using the Stepwise Approach and Prognostic Factors for Success. (April 2015) - Schreiber, Doreen; Rostock, Thomas; Fröhlich, Max; Sultan, Arian; Servatius, Helge; Hoffmann, Boris A.; Lüker, Jakob; Berner, Imke; Schäffer, Benjamin; Wegscheider, Karl; Lezius, Susanne; Willems, Stephan; et al.
<x xml:space="preserve">Abstract</x> Background— In the meantime, catheter ablation is widely used for the treatment of persistent atrial fibrillation (AF). There is a paucity of data about long-term outcomes. This study evaluates (1) 5-year single and multiple procedure success and (2) prognostic factors for arrhythmia recurrences after catheter ablation of persistent AF using the stepwise approach aiming at AF termination. Methods and Results— A total of 549 patients with persistent AF underwent de novo catheter ablation using the stepwise approach (2007–2009). A total of 493 patients were included (Holter ECGs ≥every 6 months). Mean follow-up was 59±16 months with 2.1±1.1 procedures per patient. Single and multiple procedure success rates were 20.1% and 55.9%, respectively (80% off antiarrhythmic drug). Antiarrhythmic drug–free multiple procedure success was 46%. Long-term recurrences (n=171) were paroxysmal AF in 48 patients (28%) and persistent AF/atrial tachycardia in 123 patients (72%). Multivariable recurrent event analysis revealed the following factors favoring arrhythmia recurrence: failure to terminate AF during index procedure (hazard ratio [HR], 1.279; 95% confidence interval [CI], 1.093–1.497; P=0.002), number of procedures (HR, 1.154; 95% CI, 1.051–1.267; P=0.003), female sex (HR, 1.263; 95% CI, 1.027–1.553; P=0.027), and the presence of structural heart disease (HR, 1.236; 95% CI, 1.003–1.524; P=0.047). AF termination was correlated with a higher rate of consecutive procedures because of atrial tachycardia recurrences (P=0.003; HR, 1.71; 95% CI, 1.20–2.43). Conclusions— Catheter ablation of persistent AF using the stepwise approach provides limited long-term freedom of arrhythmias often requiring multiple procedures. AF termination, the number of procedures, sex, and the presence of structural heart disease correlate with outcome success. AF termination is associated with consecutive atrial tachycardia procedures.